Fcγ receptor type IIIA polymorphism influences treatment outcomes in patients with rheumatoid arthritis treated with rituximab. Issue 6 (25th February 2012) - Ruyssen-Witrand, A; Rouanet, S; Combe, B; Dougados, M; Le Loët, X; Sibilia, J; Tebib, J; Mariette, X; Constantin, A
Abstract : Objective: To assess the association between a single nucleotide polymorphism in the gene of FCGR3A and the response to treatment with rituximab (RTX) in rheumatoid arthritis (RA). Methods: SMART is a randomised open trial assessing two strategies of re-treatment in patients responding to 1 g infusion of RTX with methotrexate on days 1 and 15 after failure, intolerance or contraindication to tumour necrosis factor (TNF) blockers. Among the 224 patients included, 111 could be genotyped and were included in an ancillary study of SMART. Univariate and multivariate analyses adjusted on disease activity score on 28 joints were performed to assess whether FCGR3A -158V/F polymorphism was associated with European League Against Rheumatism response at week 24. Results: Among the 111 patients, 90 (81%) were responders of whom 30 (27%) were good responders. V allele carriage was significantly associated with a higher response rate (91% of responders vs 70%, OR 4.6 (95% CI 1.5 to 13.6), p=0.006). These results were also confirmed in rheumatoid factor-positive patients (93% vs 74%, p=0.025). In multivariate analysis, V allele carriage was independently associated with response to RTX (OR 3.8 (95% CI 1.2 to 11.7), p=0.023). Conclusion: The 158V/F polymorphism of FCGR3A seems to influence the response to RTX in patients with RA after failure, intolerance or contraindication to TNF blockers.